"Antagonistic" cooperation of control regions in bilingual language production: An effective connectivity study. (12th March 2022) - Li, Shijie; Li, Le; Zou, Lijuan; Yan, Xin; Zhang, Juan; Yang, Menghan; Ding, Guosheng
Abstract: The dorso-lateral prefrontal cortex (DLPFC) and the anterior cingulate cortex (ACC) are two main regions that support bilingual language control during language production. Previous studies have suggested that the regions work together in language control processes. However, how they cooperate with each other during bilingual language production is far from clear. We addressed this issue by recruiting bimodal bilingual participants whose two languages could be separated at a neural level. Functional magnetic resonance imaging scans were acquired from the participants as they performed a dual-language production task and a spoken-production task. Dynamic causal modelling (DCM) was used to analyse the effective connectivity between the ACC and the DLPFC as well as the causal relationships among the control regions and language regions. We found that the ACC had positive effective connectivity to the DLPFC, left precentral gyrus and left superior temporal gyrus, while the DLPFC had negative effective connectivity to the other three regions. A similar pattern of effective connectivity between the control regions and language regions was also found in the spoken-production task. These results showed that the ACC may promote the production of the target language, while the DLPFC has an inhibitory effect in language production. The findings suggest an antagonistic relationship between the DLPFC and ACC that cooperatively ensures fluent language production in bilinguals. Highlights: We addressed how the control regions interact with the language regions during bilingual language production. The anterior cingulate cortex promotes the production of the target language. The dorso-lateral prefrontal cortex has inhibitory effects on other regions in the language control network. Antagonistic and cooperative relationship between these control regions ensures fluent language production in bilinguals.